2021
DOI: 10.1186/s42269-021-00521-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sulfur coated urea and algae fertilization on productivity of some leguminous crops in sandy soils

Abstract: Background This studies the influence of algae and coated urea fertilization on the productivity of some leguminous crops in order to reach the best methods of fertilization to get on highest productivity in sandy soils. Results The results proved that both yield and its components a better result in the focus of the SCU + algae than utilizing sulfur-coated fertilizers and algae in both seasons. A large amount extreme yield and straw yield were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…To our knowledge, only one study has so far evaluated the impacts of sulfur and algae fertilization on the productivity of soybean (Glycine max (L.) Merrill) and mung bean (Vigna radiata (L.) Wilczek) in Egypt. The results showed that compared with the single application of S 0 , MA, or the control, under the condition of combined application of S 0 and MA, the yields of soybean and mung bean were significantly increased, and the protein, carbohydrate, and oil contents also increased accordingly [12]. However, the effects of S 0 -MA interaction on soils have not been reported yet.…”
Section: Mcda000762 11(3)2022mentioning
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, only one study has so far evaluated the impacts of sulfur and algae fertilization on the productivity of soybean (Glycine max (L.) Merrill) and mung bean (Vigna radiata (L.) Wilczek) in Egypt. The results showed that compared with the single application of S 0 , MA, or the control, under the condition of combined application of S 0 and MA, the yields of soybean and mung bean were significantly increased, and the protein, carbohydrate, and oil contents also increased accordingly [12]. However, the effects of S 0 -MA interaction on soils have not been reported yet.…”
Section: Mcda000762 11(3)2022mentioning
confidence: 95%
“…C. However, the S 0 application may cause soil sulfur enrichment (i.e., an increase in SO 4 2 -), which in turn increases soil sulfate levels [4,12], and reduces crop nitrogen uptake and crop yield [13][14][15].…”
Section: Mcda000762 11(3)2022mentioning
confidence: 99%